FENOMENA TAWURAN REMAJA DAN POTENSINYA SEBAGAI SUMBER BAHAN AJAR SOSIOLOGI KELAS XI SMA (STUDI KASUS DI MUNCAR, BANYUWANGI, JAWA TIMUR) - Arvitria, Devi Wina; Sendratari, Luh Putu; Yasa, I Wayan Putra (Jurnal Pendidikan Sosiologi Undiksha, 2024)
This study aims to find out the background of the emergence of the phenomenon of teenage brawls in Muncar, Banyuwangi, East Java; to find out the impact of the phenomenon of teenage brawls in Muncar, Banyuwangi, East Java; to find out the elements contained in the phenomenon of teenage brawls in Muncar, Banyuwangi, East Java which can potentially be used as a source of teaching materials. This research uses a case study approach with a qualitative research type. Data collection methods used in the form of interviews, observation and study of documents. The findings from this study are: (1) the phenomenon of teenage brawls is caused by internal factors, external factors, situational factors and non-realistic conflicts, (2) the phenomenon of teenage brawls has a negative impact in the form of labeling and positive in the form of group solidarity, (3) sources teaching materials that can be used are in the form of handouts supplemented by the factors that cause brawls, conflict theory and the resulting impacts.